Pengaruh Campuran Consol N11 LN dan Consol SG Pada Kuat Tekan dan Serapan Air Self Compacting Concrete (SCC) - Edi Virlade; Fathoni Usman; Debby Sinta Devi (Jurnal Konstruksi, 2025)
Self-Compacting Concrete (SCC) is a type of concrete capable of compacting itself without the use of vibrators, characterized by a high slump and the ability to flow under its own weight to fill formwork completely without segregation, thereby simplifying the construction process. The materials used to produce SCC include fine aggregates, coarse aggregates, water, and cement, combined with admixtures in the form of superplasticizers. The superplasticizers added in this study were Consol SG at 0.3% and Consol N11 LN at variations of 0.6%, 1.4%, and 2%. Workability test results for SCC indicated slump flow values of 39.17 cm for 0.6% SCC, 56.72 cm for 1.4% SCC, and 61.24 cm for 2% SCC. L-Shape Box tests yielded results of 0.067 for 0.6% SCC, 0.949 for 1.4% SCC, and 0.987 for 2% SCC. The V-Funnel Test produced times of 32 seconds for 0.6% SCC, 11 seconds for 1.4% SCC, and 8 seconds for 2% SCC. Compressive strength testing of normal concrete showed values of 22.36 MPa at 7 days, 28.79 MPa at 14 days, and 35.28 MPa at 28 days. For SCC with 0.6% admixture, compressive strengths were 23.85 MPa at 7 days, 29.58 MPa at 14 days, and 36.17 MPa at 28 days. SCC with 1.4% admixture yielded compressive strengths of 25.27 MPa at 7 days, 30.16 MPa at 14 days, and 38.26 MPa at 28 days. SCC with 2% admixture reached compressive strengths of 28.04 MPa at 7 days, 33.62 MPa at 14 days, and 38.63 MPa at 28 days. Water absorption tests at 28 days showed values of 120 g for normal concrete, 110 g for SCC with 0.6% admixture, 100 g for SCC with 1.4% admixture, and 110 g for SCC with 2% admixture.